Fuzzy logic model to support risk assessment in innovation ecosystems - Abreu, António (2018)
Nowadays, enterprises in global markets must achieve high levels of performance and competitiveness to stay “alive". According to several authors and as frequently mentioned by reports of practical case studies, one of the most relevant sources of competitive advantage is the innovation capacity. The identification and quantification of the existing or potential innovation risks in a collaborative environment, is an important element for the wide adoption of the innovation ecosystem paradigm. However, models to understand the innovation risks in a collaborative environment are lacking. To address this issue, this paper introduces an approach based on a qualitative assessment, including a quantitative basis, whose development was supported by fuzzy logic for analyzing the level of risk in co-innovation projects. Finally, based on experimental results from a Portuguese collaborative network, a discussion about the benefits and challenges found are discussed.